NMDA Reduces Tau Phosphorylation in Rat Hippocampal Slices by Targeting NR2A Receptors, GSK3β, and PKC Activities - Audrée De Montigny; Ismaël Elhiri; Julie Allyson; Michel Cyr; Guy Massicotte (Neural Plasticity)
The molecular mechanisms that regulate Tau phosphorylation are complex and currently incompletely understood. In the present study, pharmacological inhibitors were deployed to investigate potential processes by which the N-methyl-D-aspartate (NMDA) subtype of glutamate receptors modulates Tau phosphorylation in rat hippocampal slices. Our results demonstrated that Tau phosphorylation at Ser199-202 residues was decreased in NMDA-treated hippocampal slices, an effect that was not reproduced at Ser262 and Ser404 epitopes. NMDA-induced reduction of Tau phosphorylation at Ser199-202 was further promoted when NR2A-containing receptors were pharmacologically isolated and were completely abrogated by the NR2A receptor antagonist NVP-AAM077. Compared with nontreated slices, we observed that NMDA receptor activation was reflected in high Ser9 and low Tyr216 phosphorylation of glycogen synthase kinase-3 beta (GSK3β), suggesting that NMDA receptor activation might diminish Tau phosphorylation via a pathway involving GSK3β inhibition. Accordingly, we found that GSK3β inactivation by a protein kinase C- (PKC-) dependent mechanism is involved in the NMDA-induced reduction of Tau phosphorylation at Ser199-202 epitopes. Taken together, these data indicate that NR2A receptor activation may be important in limiting Tau phosphorylation by a PKC/GSK3β pathway and strengthen the idea that these receptors might act as an important molecular device counteracting neuronal cell death mechanisms in various pathological conditions.